Evaluating Medicinal Plants for Anticancer Activity - Elisha Solowey; Michal Lichtenstein; Sarah Sallon; Helena Paavilainen; Elaine Solowey; Haya Lorberboum-Galski (The Scientific World Journal)
Plants have been used for medical purposes since the beginning of human history and are the basis of modern medicine. Most chemotherapeutic drugs for cancer treatment are molecules identified and isolated from plants or their synthetic derivatives. Our hypothesis was that whole plant extracts selected according to ethnobotanical sources of historical use might contain multiple molecules with antitumor activities that could be very effective in killing human cancer cells. This study examined the effects of three whole plant extracts (ethanol extraction) on human tumor cells. The extracts were from Urtica membranacea (Urticaceae), Artemesia monosperma (Asteraceae), and Origanum dayi post (Labiatae). All three plant extracts exhibited dose- and time-dependent killing capabilities in various human derived tumor cell lines and primary cultures established from patients’ biopsies. The killing activity was specific toward tumor cells, as the plant extracts had no effect on primary cultures of healthy human cells. Cell death caused by the whole plant extracts is via apoptosis. Plant extract 5 (Urtica membranacea) showed particularly strong anticancer capabilities since it inhibited actual tumor progression in a breast adenocarcinoma mouse model. Our results suggest that whole plant extracts are promising anticancer reagents.